INCREASING STUDENT LEARNING OUTCOMES THROUGH APPLICATION OF PROBLEM SOLVING MODELS BASED ON SCIENTIFIC MATERIAL MOVEMENT SYSTEMS IN CLASS XI MIPA 1 SMA NEGERI 1 MOJOSARI - Susi Triwahyuni (Sean Institute, 2022)
In Biology subject, there is material that explains the movement system in humans. This material is one of the essential materials that must be mastered by students. The level of mastery of the material can be seen through student learning outcomes. Preliminary observation results in XI MIPA 1 which obtained a daily test score of more than 50% was not complete in learning . The number of students who have not completed is 1 2 students with a percentage of 60% completeness. Based on this description, it shows that the learning outcomes of the motion system material do not reach the minimum completeness criteria. The low learning outcomes are due to the application of inappropriate learning methods, passive students in learning, no assessment of assignments. The purpose of this study was to analyze the increase in learning outcomes for class XI MIPA 1 , through the application of scientific-based problem solving methods. To improve student learning outcomes in motion systems material , a classroom action research was conducted which consisted of two cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. The subjects of this study were students of class XI MIPA 1 2019/2020 academic year. The data collection instrument in this study was an evaluation question for the cognitive domain which was carried out at the end of each cycle. Based on the results and discussion, it can be concluded that learning using problem solving provides convenience for teachers in learning, makes learning centered on students, completes learning outcomes, and can teach and train students' character behavior. Student activity reached 85.26% in the first cycle and rose to 92.22%. In the aspect of scientific behavior both cycles are in the good category. Completeness of learning outcomes also shows an increase, from 74.3% in the first cycle to 94.3% in the second cycle .